Synthesis and Characterization of Iron Oxide Nanoparticles by Using Callistemon viminalis Flowers Extract: An Eco-Friendly Approach with Promising Antioxidant Activities - Shweta Bansal; Ruchi Bharti; Ajay Thakur; Monika Verma; Renu Sharma (Orbital: The Electronic Journal of Chemistry)
The present research article introduces a novel, environmentally friendly method for synthesizing ironoxide nanoparticles (IONPs) utilizing Callistemon viminalis flowers extract as both a reducing and capping agent. This approach not only offers a sustainable and cost-effective alternative to conventional synthesis methods but also harnesses the inherent phytochemical potential of the plant extract. The synthesized IONPs underwent comprehensive characterization using various analytical techniques including X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and dynamic light scattering (DLS) to elucidate their structural, morphological, and chemical properties. Subsequently, the synthesized IONPs were evaluated for their potential antioxidant properties. The research findings contribute valuable insights into the synthesis process, structural characteristics, and antioxidant efficacy of the synthesized nanoparticles, offering promising avenues for addressing both health and environmental challenges with innovative solutions.